APPLICATION OF SPATIAL ANALYSIS TECHNIQUE IN SEARCHING BEHAVIORS RESEARCH OF INSECTS: A CASE STUDY OF STETHORUS PARAPAUPERCULUS - J. Y; Chen; G. C. Ma; F. P. Zhang; Y. G. Fu (Journal of Animal and Plant Sciences, 2015)
In this study, the spatial behaviors of insects’ searching track were investigated. Spatial analysis techniques were employed to extract spatial attribute information from the prey-searching tracks of Stethorus parapauperculus Pang. The variations in the searching distance and searching angle before and after feeding were compared. The results indicated that the S. parapauperculus tended to move along straight lines and form acute angles before feeding; and the track points were mainly concentrated in the peripheral regions of the observation area. The subjects searching distances between adjacent tracking points of before feeding were generally longer than after feeding. After feeding, the subjects changed directions more frequently, resulting in more circuitous movement tracks and increased searching angles. In particular, the subjects’ movements were mostly concentrated in the areas surrounding the initial prey sightings. The parameters of the movement tracks were easily obtained through spatial analysis techniques; thus a new method of studying insect behavioral ecology was provided.
Keywords: spatial analysis; searching behavior; Arc GIS; Stethoruspara pauperculus Pang